Primary health care for people with an intellectual disability: an exploration of consultations, problems identified, and their management in Australia. Issue 5 (24th January 2017) - Weise, J.; Pollack, A.; Britt, H.; Trollor, J. N.
Abstract: Background: People with an intellectual disability (ID) have more complex and different patterns of health care needs than the general population. They experience a greater burden of multi‐morbidity, high levels of undetected and unmanaged health issues, and premature mortality than the general population. Primary care has a key role in the health care of people with an ID. Currently, very little is known about the consultation type and length, problems managed, and how general practitioners (GPs) manage these problems for people with an ID compared with the general population. This information would provide valuable insights into how GPs are achieving the health guidelines and facilitating people with an ID to achieve the highest attainable standard of health. Methods: A secondary analysis of data was collected from January 2003 to December 2012 from the Bettering the Evaluation and Care of Health (BEACH) programme. Consultation type, consultation length in minutes, problem(s) managed during the consultation, medications, treatments provided, and referrals made, pre and post age–sex standardisation, at all GP encounters with people identified in the encounter record as having an ID ('ID' encounters, n  = 690) were compared with those at 'non‐ID' encounters ( n  = 970 641). Statistical significance was tested with 95% confidence intervals. Results: This study identified significant differences in consultation types, consultation length, problem(s) managed during the consultation, medications, treatments provided, and referrals made at 'ID' encounters compared with 'non‐ID' encounters. 'ID' encounters had more indirect encounters, longer consultations, more problems managed, but an under management of common health conditions in people with an ID. Administrative rather than medically related actions dominated clinical treatments for people at 'ID' encounters, and they received fewer procedural treatments, referrals to specialists, and medications compared with those at 'non‐ID' encounters. Conclusion: The significant differences in consultations, problems identified and managed suggest that GPs may require additional support to (1) identify and manage common medical conditions experienced by people with an ID; (2) manage the increased time required for consultations; and (3) directly consult with people with an ID. Further research is required to determine why GPs managed problems in a significantly different way for people with an ID.